BOOK REVIEWS (Journal of Finance, 1952)
Book reviewed in this article: Corporation Trust and Company . By C. A. C ooke. Cambridge, Mass.: Harvard University Press, 1951. Pp. 206. $3.00. Direct Placement of Corporate Securities . By E. R aymond C orey . Boston: Harvard University Graduate School of Business Administration, Division of Research, 1951. Pp. x+233. $3.50. Investments for Professional People . By R obert U. C ooper , M.D. New York: Macmillan Co., 1951. Pp. xvi+342. $4.00. The Stock Market . By C harles A mos D ice and W ilford J ohn E iteman . Third edition; New York: McGraw‐Hill Book Co., 1952. Pp. xii+460. $6.00. Security Analysis . By B enjamin G raham , D avid L. D odd , and C harles T atham , J r. Third edition; New York: McGraw‐Hill Book Co., 1951. Pp. xiii+770. $8.00. Federal Reserve Policy‐Making . By G. L. B ach . New York: Alfred A. Knopf, 1950. Pp. xvii+282. $3.00. The Economics of Armament Inflation . By J ules B ackman . New York: Rinehart and Co., Inc., 1951. Pp. xvi+234. $1.75. Prices and Inflation during the American Revolution . By A nne B ezanson . Philadelphia: University of Pennsylvania Press, 1951. Pp. xvi+362. Studies in Income and Wealth . By the C onference on R esearch in I ncome and W ealth . New York: National Bureau of Economic Research, 1952. Pp. x+276. $3.50. The Economics of Mobilization and Inflation . By S eymour E. H arris . New York: W. W. Norton Co., 1951. Pp. xii+308. $5.50. Defense without Inflation . By A lbert G. H art . New York: Twentieth Century Fund, 1951. Pp. xiv+186. $2.00. Life Insurance . By J oseph B. M aclean . New York: McGraw‐Hill Book Co., 1951. Pp. xiii+697. $4.50. Taxation and the American Economy . By W illiam H. A nderson . New York: Prentice‐Hall Co., Inc., 1951. Pp. xxi+598. $6.00. Fraud under Federal Tax Law . By H arry G raham B alter . Chicago: Commerce Clearing House, Inc., 1951. Pp. 330. $6.00. Effects of Taxation: Corporate Mergers . By J. K eith B utters , J ohn L intner , and W illiam L. C ary . Boston: Harvard University Graduate School of Business Administration, 1951. Pp. xviii+364. $4.25. The Liquor Tax in the United States . By T un Y uan H U . New York: Columbia University Graduate School of Business, 1950. Pp. viii+188. $2.75. Taxation in Canada . By J. H arvey P erry . Toronto: University of Toronto Press, 1951. Pp. xiii+409. $6.00. The Soviet Financial System . By M ikhail V. C ondoide . Columbus, Ohio: The Bureau of Business Research, College of Commerce and Administration, Ohio State University, 1951. Pp. xiii+230. $4.00. International Economics . By S tephen E nke and V irgil S alera . Second edition; New York: Prentice‐Hall Co., Inc., 1951. Pp. ix+724. $5.00. History and Policies of the Home Owners' Loan Corporation . By C. L owell H arriss . New York: National Bureau of Economic Research, 1952. Pp. xix+204. $3.00.